1994
DOI: 10.1016/0043-1354(94)90308-5
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of contaminated subsurface soils with enriched indigenous microbes to enhance bioremediation rates

Abstract: The inoculation of subsurface soils with enriched indigenous microbes to enhance bioremediation is described. The technique, designed to rapidly increase subsurface populations of specific microorganisms, is tested in laboratory soil columns using benzene, toluene and xylene as organic target compounds and a natural aquifer sand as a subsurface medium. A short biologically active carbon adsorber is demonstrated to be an efficient reactor system for the growth, acclimation and enrichment of indigeous microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…On one hand, it seems that there is a positive correlation between the population density of GFP-tagged strain and the ONBA removal rate, suggesting that the bioaugmentation was effective but ephemeral that is often experienced in the bioreactors, and biological supplement for such systems have to be added on a regular basis in order to assure continuous treatment efficacy. On the other hand, the result support the idea that natural uncontaminated systems contain sufficient genetic diversity to make them valid choices for the removal of xenobiotics, either by metabolism or co-metabolism, after an adequate exposure time [8,32,33]. Moreover, the acclimatized nonbioaugmented system owns more stable sludge floc structure and operation performance than the bioaugmented one, which is especially true under shocks.…”
Section: Discussionsupporting
confidence: 86%
“…On one hand, it seems that there is a positive correlation between the population density of GFP-tagged strain and the ONBA removal rate, suggesting that the bioaugmentation was effective but ephemeral that is often experienced in the bioreactors, and biological supplement for such systems have to be added on a regular basis in order to assure continuous treatment efficacy. On the other hand, the result support the idea that natural uncontaminated systems contain sufficient genetic diversity to make them valid choices for the removal of xenobiotics, either by metabolism or co-metabolism, after an adequate exposure time [8,32,33]. Moreover, the acclimatized nonbioaugmented system owns more stable sludge floc structure and operation performance than the bioaugmented one, which is especially true under shocks.…”
Section: Discussionsupporting
confidence: 86%
“…However, during the fifth week, enhanced degradation was observed in one of the reactors, probably due to the enrichment of indigenous bacteria with degradative capacities. It has been reported that in some cases indigenous bacteria become capable of removing xenobiotics after a long exposure time, either by metabolism or by cometabolism (28,32,47,53). However, in our parallel SCAS reactors, the differences in degradation rates between the inoculated and control reactors were striking and stable over a prolonged time period, suggesting that the bioaugmentation was effective and not ephemeral.…”
Section: Discussionmentioning
confidence: 44%
“…According to Vogel and Walter (2001), BA can be divided into three classes: one type is the enrichment or isolation of microorganisms from the target site, their subsequent culturing and reinoculation; in the second type of BA, isolates or enrichments are not inoculated to the source of the original culture; and the third type is the use of constructed or force-mutated microorganisms. ABA has the same concept as the first type of BA defined by Vogel and Walter (2001) and this method has also been called "reinoculation" (Weber and Corseuil 1994).…”
Section: Past and Present Autochthonous Bioaugmentationmentioning
confidence: 99%
“…Similarly, a petrochemical waste (Vecchioli et al 1990), benzo[a]pyrene and carbazol (Grosser et al 1991), and various oil products such as gasoline and diesel fuel (Belloso 2003a) present as contaminants in soils were efficiently degraded ex situ by indigenous soil bacteria in microcosms enriched from the contaminated soils. Weber and Corseuil (1994) used laboratory soil columns artificially contaminated with benzene, toluene and xylene to rapidly increase the populations of specific microorganisms. Reinoculation of the soils with these microorganisms enhanced the rate of degradation of the contaminants in the soil.…”
Section: Past and Present Autochthonous Bioaugmentationmentioning
confidence: 99%